Implementation of Sustainable PBL towards Affordable and Clean Energy: Industry, Innovation - Him Bindu, E.; Dora, Radhika; Krishna, D.; Srikanth Goud, B. (Journal of Engineering Education Transformations, 2025)
Sustainable development is way of life need to adopt to preserve resources for future generation. Adopting this idea will help to keep the ecosystem in balance. Sustainable development is defined as development that fully recognizes, supports human needs while explicitly endorsing ecological limitations within the framework of economic activity. The Sustainable Development Goals (SDGs) are examined in this study as a critical international framework for addressing environmental, socioeconomic issues. It breaks down intricacies of SDG implementation by carefully examining advancements, obstacles, strategic paths. This research work focuses on different Sustainable Project based learning methods of Industry, Innovation, Infrastructure; Sustainable Cities. To obtain clean energy, industry innovation education plays key role in energy transition by raising awareness, training, sector players to promote renewable energies. In order to give high-quality education on renewable energy, it is imperative that educators stay up to date on current industry trends, emerging technology, and successful pedagogical approaches. This can be achieved through ongoing professional development programmers. For energy transition a continuous monitoring and SDG indicators, baseline assessment, promotion of energy policies, examining investment trends, regulatory frameworks, public-private partnerships supporting industrial development, innovation ecosystems are required. For this a new project-based learning (PBL) must be involved to obtain specified goals. PBL teachers should support acquisition of interdisciplinary learning goals via a variety of learning activities that include direct instruction organized under an inquiry, typically with significant student voice.